Hukum dan Etika Berinteraksi Melalui Media Sosial Menurut Islam - Nanang Abdillah (Program Studi Pendidikan Agama Islam, 2021)
Social media is an electronic media, which is used to participate, share, and create content in the form of blogs, social networks, forums, virtual worlds, and other forms. On social media people are free to interact and interact. For those who care about the limits of the Shari'a, they will obey the Shari'a rules. For those who do not, then the rules of the Shari'a will be hit. Lately, social media has become increasingly out of control, even at the stage of being biased into plunging a person into the devil's strong trap. Why not, social media (social media) which should be used as a vehicle to strengthen ties of friendship, share experiences and news that is enlightening and soothing, is actually being used massively to spread false news to launch attacks on other parties. From the point of view of religious law, every Muslim who interacts through social media is prohibited or prohibited from producing, distributing and making accessible content/information that is not true to the public, hoaxes, backbiting, slander, namimah, disgrace, bullying, hate speech, and other things. other similar matters relating personally to other people and the general public. Meanwhile, from the point of view of Islamic ethics, social media can be used as a means to establish friendship, disseminate information, da'wah, education, recreation, and for positive activities in the fields of religion, politics, economy, and social and culture. Therefore Islam also teaches ethics in social media. Interacting through social media must be done without violating religious provisions and statutory provisions.